Robot-assisted donor nephrectomy in horseshoe kidney: Possible with indocyanine green and firefly - Swapnil Singh Kushwaha; Amit Aggarwal; Karandeep Guleria; Samit Chaturvedi; Anant Kumar (Urology Video Journal)
Introduction: Horseshoe kidney (HSK), a congenital anomaly, presents unique challenges for transplant surgeons due to its complex vascular and collecting system anatomy. The use of HSK as a donor remains controversial, although cases have been performed most frequently in deceased donor transplants, and some have even tried open and laparoscopic approaches in living donors. Typically, in these cases, the isthmus was thin, fibrous and lacked a separate blood supply. In this video, we demonstrate our technique and share the outcome of the world's first robot-assisted donor nephrectomy in HSK for parenchymatous isthmus with multiple vessels. Materials and methods: A 49-year-old female, voluntary kidney donor for her husband, was found to have HSK. The renal scan indicated equal function of both moieties. The right moiety was supplied by a main renal artery and branches of a common lower polar artery. The left moiety was supplied by a main renal artery and two accessory lower polar arteries. One common lower polar renal artery was seen arising from the anterior aspect of the aorta supplying bilateral lower poles and isthmus. She was planned for robot-assisted donor nephrectomy of the right moiety in HSK, as there were no alternate donors. Results: The main right renal artery, along with the accessory arteries to the isthmus, were dissected out. The level of demarcation over the parenchymatous isthmus was noted in firefly mode after injecting intravenous indocyanine green (ICG) dye. Pantaloon anastomosis for both accessory arteries, along with renorrhaphy of the isthmus, was done on bench. The recipient underwent an open kidney transplant; the main right renal artery was anastomosed with the right common iliac artery, and the pantaloon created was anastomosed to the right external iliac artery. The intra and postoperative courses for both donor and recipient were uneventful. Renal function remained stable in both, with no complications, throughout the follow-up of 20 months. Conclusions: Retrieving a living-donor HSK presents significant technical challenges in removing a moiety without compromising the function of the other. Given the global shortage of donor kidneys, utilizing a donor with HSK could be a viable and safe option in experienced hands. We utilized the robotic platform, enhanced with ICG and firefly mode, to successfully complete this challenging procedure.